2022
DOI: 10.3390/nu14122510
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dewaxed Coffee on Gastroesophageal Symptoms in Patients with GERD: A Randomized Pilot Study

Abstract: Gastroesophageal Reflux Disease (GERD) is multifactorial pathogenesis characterized by the abnormal reflux of stomach contents into the esophagus. Symptoms are worse after the ingestion of certain foods, such as coffee. Hence, a randomized pilot study conducted on 40 Italian subjects was assessed to verify the effect of standard (SC) and dewaxed coffee (DC) consumption on gastroesophageal reflux symptoms and quality of life in patients with gastrointestinal diseases. The assessment of patient diaries highlight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 55 publications
(63 reference statements)
0
4
0
2
Order By: Relevance
“…In contrast, one dietary intervention failed to show significant effects in GERD patients. Dietary nitrate had no significant effect on TLESR, reflux episodes, gastric pH, or reflux symptoms [32].…”
Section: Other Dietary Interventionsmentioning
confidence: 75%
“…In contrast, one dietary intervention failed to show significant effects in GERD patients. Dietary nitrate had no significant effect on TLESR, reflux episodes, gastric pH, or reflux symptoms [32].…”
Section: Other Dietary Interventionsmentioning
confidence: 75%
“…Five studies (two prospective cohort [ 14 , 38 ], two randomised crossover studies in coffee-sensitive individuals [ 39 , 40 ] and one cross-sectional study [ 41 ]) support a positive association between coffee consumption and reflux-like symptoms. However, a recent systematic review shows that the data are particularly conflicting, with multiple studies finding no increased risk of reflux-like symptoms in coffee drinkers [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…We did not identify any interventional studies assessing the effect of reduced coffee intake on symptoms. However, substitution analysis in the cohort study conducted by Mehta et al [38] showed that replacing two servings of coffee with water would reduce the risk of refluxlike symptoms [hazard ratio (HR), 0.96; 95% confidence interval (CI), 0.92-1.00] and a small, randomised study demonstrated significant symptom reduction and antacid use when coffee-sensitive individuals switched to dewaxed coffee (containing less caffeine and chlorogenic acids) [39].…”
Section: Diet and Exercise Advicementioning
confidence: 99%
“…Apesar dos compostos bioativos presentes no café serem relacionados à diminuição no risco de câncer, diabetes, doenças hepáticas e cardiovasculares, foi observado que também Brazilian Journal of Health Review, Curitiba, v. 7, n. 1, p. 2170-2193, jan./fev., 2024 servem de possíveis indutores para os sintomas da DRGE, como azia e regurgitação. Sendo assim, ao estudar esse grão, foi percebido que seus elementos cerosos, localizados na parte cortical, precisam de condições ideais para serem absorvidos, caso contrário podem causar irritação da mucosa (Polese, et al, 2022). O café "desparafinado" é livre desses componentes irritativos e rico nos preventivos, o que ameniza os sintomas negativos e mantém seu efeito benéfico.…”
Section: Dietaunclassified